Pengolahan Air Limbag dan Produksi Listrik Secara Simulasi Oleh Microbial Fuel Cells (MFCS) - Timotius, Kris Herawan (Teknik dan Ilmu Komputer, 2017)
The need of electricity and wastewater treatment are two main aspects of modern society. Microbial Fuel Cells (MFCs) has the potential to solve these two problems simultaneously. Wastewater treatment with MFCs Technology at the same time can produce electrical energy. This research article is written to describe the potential of MFCs to treat wastewater from various sources, such as from household or industry, andÃÂ  to produce electrical energy. The MFCs open system can be applied for the above purposes. This technology resembles the wastewater treatment in the nature. Our nature has the capacity to treat wastewater, such as ponds, lakes, and wetlands. These habitats have two phases: the sediment phase (lower) and aqueous phase (upper). The SMFCs resembles this natural process. In those phases, the anode is placed in the sediment phase, and cathode is placed in aqueous phase. If both electrodes are connected, then electrical energy is produced.ÃÂ  ÃÂ Keywords: alternative energy, MFCs, Microbial Fuel Cells, wastewater treatment, electricity production, SMFCs, Sediment Microbial Fuel Cells